Validity of the ‘Dunya Hejo (Du-Jo)’ Problem-Based Learning E-Worksheet on Climate Change and Global Warming - Devi Yulianty Surya Atmaja; Achmad Samsudin (Online Learning In Educational Research (OLER), 2024)
Climate change and global warming are critical environmental issues that require effective educational strategies to enhance students' understanding. Student worksheets can play a significant role in facilitating active learning on these topics. This research aims to determine and describe the validity of the "Dunya Hejo (Du-Jo)" E-Worksheet on climate change and global warming. The research method used is the Educational Design Research Plomp model. There are 3 research stages, but this research only consists of 2 stages, namely the initial investigation stage and the design stage. Because this research only describes the validity of the "Dunya Hejo (Du-Jo)" E-Worksheet. Validation was conducted by two media experts, two material experts, and five teachers. This e-worksheet will be used by high school students in class X. Validation results from the experts and teachers indicated that the "Dunya Hejo (Du-Jo)" e-Worksheet received excellent ratings for software engineering, visual communication, and learning design. Therefore, this e-worksheet is suitable for use in climate change and global warming learning activities for class X high school students.